Daisy Hontiveros Avellana first lady of Philippine theater - National Commission for Culture and the Arts; Marasigan, Dennis; Adlawan, Irma.; Avellana, Jose Mari.; De la Cruz, Libertine Santos; Cultural Center of the Philippines (Pasay City Cultural Promotions Division, Cultural Resources Dept., Cultural Center of the Philippines, 2002)
Documents Daisy Hontiveros Avellana's efforts as actor, director, producer and writer. She was a recipient of numerous prizes, honors and awards, including Gawad Siglo ng Aliw, Tandang Sora Award for Theater, the Patnubay ng Sining at Kalinangan Award, Gintong Ina Award for Theater, Gawad CCP Para sa Sining and the CCP Centennial Honors for the Arts.
"Avellana : national artist for theater"--Cover.
Writers: Dennis Marasigan, Irma Adlawan ; director: Jose Mari Avellana ; music: Lamberto V. Avellana, Jr. ; producer: Libertine dela Cruz.